PENGARUH HARGA, CITRA MEREK, KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK RABBANI CABANG PONTIANAK (STUDI EMPIRIS PADA KONSUMEN RABBANI KOTA PONTIANAK) - admin, RABIATUL ADAWIYAH B11112112 (Jurnal Manajemen Update, 2016)
The purpose of this research is to investigate the influence of price, brand images, product qualities, and product designs towards a buying decision of Rabbani product branch Pontianak. In this research, the population was consumers of Rabbani product in Pontianak. 100 respondents then were selected to represent the research sample. The method use for this research was an associative study, while questionnaires were used for a data-collection purpose. The tool for analysis was IBM SPSS 21. The pricing variable was measured through several indicators i.e. an affordable price, the suitabilly of price and quality, the pricing capability to complete, and the suitability of price and produc benefits. The brand-image variable was measured by several indicators, for example the product recognition, roputation, and attractiveness. A product quality variable was assessed through endurance and excellence. A design variable was measured by the model update, design variation, and product?s capability of fitting market development. A buying decision variable was judged by the demand for products, confidence to buy products, careful considerations, and stsbility to buy product. As a result of discussion, it can be concluded the pricing variable (X1) and the brand-image variable (X2) did not significantly influence towards a buying decision towards products (Y). It means that price and brand quality could not force the respondent?s desire, at least in this sample, to make a decision to buy products. On the other hand, the product-quality variable (X3) and product-design variabel (X4) did give a significant influence towards the buying decision toward product (Y). Itmeans the product quality and product design could encourage respondents in this sample to make a decision to buy products. Key words : Price, Brand Image, Product Quality, Product Design, Buying Decision